Evaluation of early malignant Changes of dentigerous Cyst into central mucoepidermoid carcinoma by immunohistochemical of Ki67, p53, bcl2 and periodic acid Schiff mucin stain (Journal of Academic Research, 2025)
Odontogenic cysts, such as dentigerous cysts, are common jaw lesions, often associated with impacted teeth and presenting as asymptomatic radiolucencies. While typically benign, they may undergo neoplastic transformation into aggressive lesions like ameloblastomas or central mucoepidermoid carcinomas (MEC). This study analyzed a histopathological lesion initially diagnosed as a dentigerous cyst using H&E, p53, Ki-67, Bcl-2, PAS, and Mucicarmine staining to assess cellular composition and malignant potential. Histological findings revealed a stratified squamous epithelial lining with mucous metaplasia, chronic inflammation, and an intact basement membrane. Immunohistochemistry showed low p53 expression, basal-layer Ki-67 positivity, and localized Bcl-2 staining, suggesting low proliferative activity. PAS staining confirmed basement membrane integrity, while Mucicarmine detected focal mucous cell metaplasia. The presence of mucous, epidermoid, and intermediate cells raised suspicion of early-stage MEC; however, the absence of significant atypia or diffuse proliferative markers supported the diagnosis of a dentigerous cyst with mucous metaplasia. A rare case of low-grade intraosseous MEC was identified in a 47-year-old woman, progressing untreated for two years before symptomatic presentation. Surgical enucleation and histopathological analysis confirmed epithelial dysplasia and mucous metaplasia, consistent with MEC. A four-year follow-up showed complete bone regeneration without recurrence. This case emphasizes the necessity of early diagnosis, routine monitoring, and comprehensive histopathological evaluation of odontogenic cysts to prevent malignancy. Conservative management is effective for benign lesions, while molecular studies (MAML2, P63, Bcl-2 gene rearrangement) are recommended for cases with neoplastic potential.
Keywords: Dentigerous Cyst; Mucoepidermoid Carcinoma; IHC; Ki67; PAS Staining